2022
DOI: 10.1007/s00787-022-01975-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of studies on resilience and risk and protective factors for health among refugee children in Nordic countries

Abstract: The Nordic welfare model is often used as an example for the promotion of health and wellbeing, even in vulnerable groups of children, such as refugees. Nonetheless, there are no published reviews on resilience and/or risk and protective factors for physical and mental health among refugee children living in Nordic countries. In this systematic review, we identified 5181 studies on the topic, screened titles, and abstracts, viewed 632, and finally included 26 studies. These studies described 18 samples with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The results also identified being unaccompanied as a risk factor for mental health problems among refugee children. While previous research from the Nordic countries has shown varied results (Mattelin et al, 2022b), international studies have consistently indicated it as a risk factor (Fazel et al, 2012).…”
Section: Associations Between Refugees and Migrants Who Selfidentify ...mentioning
confidence: 95%
See 1 more Smart Citation
“…The results also identified being unaccompanied as a risk factor for mental health problems among refugee children. While previous research from the Nordic countries has shown varied results (Mattelin et al, 2022b), international studies have consistently indicated it as a risk factor (Fazel et al, 2012).…”
Section: Associations Between Refugees and Migrants Who Selfidentify ...mentioning
confidence: 95%
“…Prisma flow-chart diagram (Mattelin, Paidar, Söderlind, Fröberg, & Korhonen, 2022b) Notably, none of the studies explicitly examined resilience, and only a few examined into the study of risk-and protective factors, often in a vague manner. Therefore, we clarified whether the studied associations fulfilled the basic criteria for the classification of riskand protective factors.…”
Section: Figurementioning
confidence: 99%
“…It has been found that children and women constitute the group with the largest population among the refugee group that migrated to Turkey. Situations such as the detention of parents or children themselves, witnessing the loss or death of parents, and separation from families have resulted in the emergence of a series of psychological, emotional and social problems in refugee children during their migration with the impact of the war (5,6). Families and children have been reported to experience a range of mental health problems such as depression, post-traumatic stress disorder, anxiety, sleep disturbances and behavioural disorders, despite living for long periods of time in countries where they have sought asylum (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Families and children have been reported to experience a range of mental health problems such as depression, post-traumatic stress disorder, anxiety, sleep disturbances and behavioural disorders, despite living for long periods of time in countries where they have sought asylum (7)(8)(9). Systematic analyses have highlighted that children's negative experiences such as exposure to violence during migration, war experiences, losses and separations are associated with different mental health problems (5,6). While many studies in literature focus on mental health problems of refugee children, social exclusion, isolation and sleep problems have not been addressed (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The most common countries of origin for these children were Syria, Afghanistan, and Iraq (Swedish Migration Agency, 2022). Children have to flee their country of origin for numerous reasons, including armed conflicts, famine, and human right violations (Mattelin et al, 2022). Moreover, children in migration might have experienced adversities, including violent and traumatic events, both before and after fleeing their home country (Mattelin et al, 2021).…”
mentioning
confidence: 99%